Pemahaman Guru Sekolah Menengah Kejuruan Negeri 7 Palangka Raya Terhadap Strategi Teaching Factory - Sabariah Sabariah; Mazrur Mazrur; Jasiah Jasiah (Universitas Negeri Malang, 2025)
Abstract: The purpose of this study was to identify and describe factually, accurately, and systematically (1) Teachers' understanding of the teaching factory (TeFa) model and (2) Inhibiting and supporting factors in the implementation of TeFa in the Food Crops and Horticulture (ATPH) agribusiness expertise program at SMK Negeri 7 Palangka Raya. This study used a descriptive quantitative approach. The study's subjects included the principal, the head of the expertise program, teachers, and employees at SMK Negeri 7 Palangka Raya. Data collection was conducted through questionnaire. Data analysis used descriptive analysis methods. The study's results showed that (1) some teachers have a good understanding of the concept, objectives, and steps involved in implementing TeFa. In contrast, others remain confused about integrating TeFa into the learning process. (2) The implementation of TeFa in the ATPH expertise program at SMK Negeri 7 Palangka Raya is running because of supporting factors including: (a) The principal has entrepreneurial motivation and TeFa development; (b) some TeFa managers and instructors (teachers and employees) have attended industry training; (c) the existence of production/business units; (e) support from the business and industry (DUDI) partners even though the number of participating industries is still lacking. The implementation of TeFa has several obstacles, including (a) the lack of TeFa training provided, (b) limited facilities and infrastructure, (c) government funding, (d) limited cooperation with DUDI, and minimal industrial experience from managers. Keywords: teaching factory, smk, the food crops and horticulture (ATPH) Abstrak: Tujuan penelitian ini adalah untuk mengidentifikasi dan mendeskripsikan secara faktual, akurat, dan sistematis tentang: (1) Pemahaman guru mengenai model teaching factory (TeFa), dan (2) Faktor penghambat dan pendukung dalam implementasi TeFa pada program keahlian agribisnis Tanaman Pangan dan Holtikultura (ATPH) di SMK Negeri 7 Palangka Raya. Penelitian ini menggunakan pendekatan kuantitatif deskriptif. Objek penelitian adalah kepala sekolah, ketua program keahlian, guru, dan pegawai di SMK Negeri 7 Palangka Raya. Pengumpulan data dilakukan melalui kuesioner. Analisis data menggunakan metode analisis deskriptif. Hasil penelitian menunjukkan bahwa (1) Sebagian guru telah memahami konsep, tujuan, dan langkah-langkah implementasi TeFa dengan baik, namun sebagian lainnya masih mengalami kebingungan dalam mengintegrasikan TeFa ke dalam proses pembelajaran. (2) Pelaksanaan TeFa pada program keahlian ATPH di SMK Negeri 7 Palangka raya berjalan karena adanya faktor pendukung antara lain: (a) Kepala Sekolah memiliki motivasi kewirausahaan dan penembangan TeFa; (b) sebagian pengelola dan instruktur TeFa (guru dan pegawai) pernah mengikuti pelatihan di industri; (c) terdapatnya unit produksi/bisnis; (e) adanya dukungan dari dunia usaha dan industri (DUDI) mitra meskipun jumlah industri yang berpartisipasi masih kurang. Pelaksanaan TeFa memiliki beberapa hambatan antara lain: (a) masih minimnya pelatihan TeFa yang diberikan; (b) adanya keterbatasan sarana dan prasarana; (c) pendanaan dari pemerintah. Kata kunci: teaching factory; smk, agribisnis tanaman pangan dan holtikultura (ATPH)